THE AVAILABILITY OF THE DOCUMENTATION REQUIREMENT TO OBTAIN THE ISO 9001:2015 CERTIFICATE IN PREFABRICATED BUILDING FACTORY- IRAQ: A CASE STUDY - Akram Omar Arslan, Mueyyed; Thiruchelvam, Sivadass; Hayder, Gasim (Proceedings on engineering sciences (Online), 2023)
The study aims to shed light on the item (documentation requirement) within one of the components of the general requirements of the international standard (ISO 9001:2015) in the prefabricated building factory in Kirkuk/ Iraq. The purpose of the study was to find out the reality of the availability and application of these requirements to obtain the certificate of international standards by indicating the levels of achievement of the documentation item, as well as an attempt to open horizons for the application of other necessary items for the factory to obtain the mentioned certificate. To achieve this goal, checklists were relied upon, which contributed to obtaining the necessary data to achieve the study objective. The study found statistical results showing that there is a large gap (70%) between the actual reality of the documentation requirement and the theoretical academic reality, and the organization must address this gap to improve its performance in obtaining the mentioned certificate. The study included proposals and recommendations, the most prominent of which was the need to establish a computerized database to collect data on the factory's operations and activities to benefit from it in future analysis and documentation processes.